2014
DOI: 10.4103/0975-7406.137418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinicopathological comparison of kerotocystic odontogenic tumor and orthokeratinized odontogenic cyst in South Indian sample population: A retrospective study over 13 years

Abstract: Aim and Methodology:The purpose of this study is to determine the prevalence of keratocystic odontogenic tumor (KCOT) and orthokeratinized odontogenic cyst (OOC), to identify their clinicopathological features among the patients by studying the biopsy specimens obtained from the archives of the Department of Oral and Maxillofacial Pathology, College of Dental Sciences, Davangere, Karnataka, India during the period of 2001-2013. Data for this study is retrieved from the case records of the patients fitting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These authors also noted that due to the aggressiveness and high recurrence rate of KCOT compared to OOC, the differentiation between them is important with respect to their treatment modalities. Their results showed that the clinical features of the two entities resembled each other but histological features were distinct [18]. Bharathi et al also published a case report of OOC and reviewed the literature [19].…”
Section: Discussionmentioning
confidence: 99%
“…These authors also noted that due to the aggressiveness and high recurrence rate of KCOT compared to OOC, the differentiation between them is important with respect to their treatment modalities. Their results showed that the clinical features of the two entities resembled each other but histological features were distinct [18]. Bharathi et al also published a case report of OOC and reviewed the literature [19].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body multinucleated giant cells arise from an inflammatory response resulting from the persistent presence of a non-phagocytable material 13 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] OKCs arise from the remnants of dental lamina and are the third-most common type of odontogenic cyst in a study from the Indian population. [ 12 ] It may present as pain in the jaw, soft-tissue swelling and paresthesia of lip/teeth or may be asymptomatic as it tends to grow in an anteroposterior direction within the medullary cavity of the bone without causing obvious bone expansion. Distinctive clinical features include potential for local destruction and a tendency for multiplicity, especially when the lesion is associated with nevoid basal-cell carcinoma syndrome syndrome.…”
Section: Introductionmentioning
confidence: 99%